Multicenter randomized controlled trial to evaluate the efficacy and tolerability of frozen gloves for the prevention of chemotherapy-induced peripheral neuropathy - Beijers, A J M; Bonhof, C S; Mols, F; Ophorst, J; de Vos-Geelen, J; Jacobs, E M G; van de Poll-Franse, L V; Vreugdenhil, G (Annals of oncology, 2020)
This study investigated the efficacy and tolerability of wearing frozen gloves (FGs) during chemotherapy to prevent chemotherapy-induced peripheral neuropathy (CIPN) as reported by patients and influence on quality of life (QoL). Cancer patients starting treatment with oxaliplatin, docetaxel or paclitaxel between February 2013 and May 2016 at the medical oncology department were eligible. Patients were randomized into groups wearing FGs on both hands during treatment and those not wearing FGs during treatment. Self-reported CIPN and QoL were measured with the European Organisation for the Research and Treatment of Cancer Quality of Life (EORTC QLQ) CIPN20 and QLQ-C30 at four time points: baseline (t ), after three cycles (t ), end of chemotherapy (t ) and after 6 months (t ). The study included 180 patients with 90 patients in both arms. They mostly underwent treatment of colorectal or breast cancer. Thirty-one patients (34%) discontinued FGs, mainly due to discomfort. Intention-to-treat analyses showed no important differences in reported EORTC QLQ CIPN20 subscales between the FG group and control group; however, the analyses showed the patients experienced reduced tingling in fingers/hands [β = -10.20, 95% confidence interval (CI) = -3.94 to -3.14, P = 0.005] and less trouble opening a jar or bottle due to loss of strength in hands (β = -6.97, 95% CI = -13.53 to -0.40, P = 0.04) in the FG group compared with the control group. Per-protocol analyses showed similar results: reduced aching or burning pain in fingers/hands (β = -4.37, 95% CI = -7.90 to -0.83, P = 0.02) and cramps in hands (β = -3.76, 95% CI = -7.38 to -0.14, P = 0.04). Differences in tingling in fingers/hands at t were clinically relevant. In addition, those treated with FGs reported overall better QoL (β = 4.79, 95% CI = 0.37 to 9.22, P = 0.03) and physical functioning (β = 5.66, 95% CI = 1.59 to 9.73, P = 0.007) than the control. No difference in dose reductions was observed. No difference in CIPN subscales was reported between intervention arms. Wearing FGs might reduce some neuropathy symptoms in the hands, potentially resulting in a better QoL; however, one-third of the FG group discontinued the study before the end of treatment. Future studies should focus on the method of limb hypothermia to prevent CIPN. NL39650.015.12.